2010
DOI: 10.1177/548.6529
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Fibrous Tumor of Small Bowel Mesentery: A Case Report and Review of the Literature

Abstract: Solitary fibrous tumor is an extremely rare clinical entity, most commonly manifested in the pleura and peritoneum. An increasing number of cases are found to occur at extrapleural sites. We report a case of solitary fibrous tumor arising from the mesentery of the small intestine. A 53-year-old man presented with a large abdominal mass which was initially thought to be a gastrointestinal stromal tumor. The tumor was successfully removed surgically and the diagnosis of solitary fibrous tumor was confirmed on im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It has been reported that SFTs are characteristically CD34 and CD99 positive, but CD117 negative. [2] CD117 antibody is the best marker to distinguish SFT from gastrointestinal stromal tumor (GIST), and immunohistochemistry for CD117 expression, especially when CD34 expression is positive, plays a very important role in the diagnosis of SFT. In the present case, the tumor was finally confirmed to be SFT by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that SFTs are characteristically CD34 and CD99 positive, but CD117 negative. [2] CD117 antibody is the best marker to distinguish SFT from gastrointestinal stromal tumor (GIST), and immunohistochemistry for CD117 expression, especially when CD34 expression is positive, plays a very important role in the diagnosis of SFT. In the present case, the tumor was finally confirmed to be SFT by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…[1] By 2008, approximately 820 cases had been reported worldwide, [2] which occurs commonly in the pleura, but also rarely in extrapleural sites. SFT in the abdomen has been sporadically reported over the past decade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Extrapleural SFT account 0.6% of all soft tissue tumors.SFT of abdominal wall are extremely rare with only 16 cases till date. [4] Name & Address of Corresponding Author Dr. Alaka Sahu, Assistant Professor, Dept of Pathology, VIMSAR, Burla, Sambalpur, Odisha, India…”
Section: Introductionmentioning
confidence: 99%
“…Currently, solitary fibrous tumor, haemangiopericytoma, lipomatous haemangiopericytoma, and giant cell angiofibroma are all lumped under the category of "extrapleural SFT". [3][4][5][6] …”
Section: Introductionmentioning
confidence: 99%